Engineering Specificity Changes on a RanBP2 Zinc Finger that Binds Single‐Stranded RNA1. (9th July 2014) - Vandevenne, Marylène; O'Connell, Mitchell R.; Helder, Stephanie; Shepherd, Nicholas E.; Matthews, Jacqueline M.; Kwan, Ann H.; Segal, David J.; Mackay, Joel P.
Abstract The realization that gene transcription is much more pervasive than previously thought and that many diverse RNA species exist in simple as well as complex organisms has triggered efforts to develop functionalized RNA‐binding proteins (RBPs) that have the ability to probe and manipulate RNA function. Previously, we showed that the RanBP2‐type zinc finger (ZF) domain is a good candidate for an addressable single‐stranded‐RNA (ssRNA) binding domain that can recognize ssRNA in a modular and specific manner. In the present study, we successfully engineered a sequence specificity change onto this ZF scaffold by using a combinatorial approach based on phage display. This work constitutes a foundation from which a set of RanBP2 ZFs might be developed that is able to recognize any given RNA sequence.